(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article analyses the most relevant aspects of the proposal for a regulation on the EU Digital COVID Certificate. Firstly, it describes the framework for the issuance, verification and acceptance of interoperable certificates on vaccination, testing and recovery. Then, the article focuses on three main aspects: (1) the role of the system of the EU Digital COVID Certificate with respect to the exercise of freedom of movement within the EU; (2) the intersections between certification, scientific knowledge and restrictions on freedom of movement adopted by the Member States; (3) data processing related to the certificates’ systems